2017
DOI: 10.1371/journal.pone.0185843
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine adjuvant MF59 promotes the intranodal differentiation of antigen-loaded and activated monocyte-derived dendritic cells

Abstract: MF59 is an oil-in-water emulsion adjuvant approved for human influenza vaccination in European Union. The mode of action of MF59 is not fully elucidated yet, but results from several years of investigation indicate that MF59 establishes an immunocompetent environment at injection site which promotes recruitment of immune cells, including antigen presenting cells (APCs), that are facilitated to engulf antigen and transport it to draining lymph node (dLN) where the antigen is accumulated. In vitro studies showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
1
21
0
2
Order By: Relevance
“…also found that the adjuvant MF59 induced the differentiation of monocytes to dendritic cells, and that these cells represented the main source of antigen‐loaded and activated antigen presenting cells within lymph nodes. Interestingly, this finding correlated with the enhanced triggering of the antigen‐specific CD4 T cell response . These findings also suggest that squalene could modify dendritic cell metabolism to process antigens by modifying reactive oxidative species.…”
Section: Squalene and The Immune Systemmentioning
confidence: 73%
See 1 more Smart Citation
“…also found that the adjuvant MF59 induced the differentiation of monocytes to dendritic cells, and that these cells represented the main source of antigen‐loaded and activated antigen presenting cells within lymph nodes. Interestingly, this finding correlated with the enhanced triggering of the antigen‐specific CD4 T cell response . These findings also suggest that squalene could modify dendritic cell metabolism to process antigens by modifying reactive oxidative species.…”
Section: Squalene and The Immune Systemmentioning
confidence: 73%
“…Squalene is present in emulsion‐based adjuvants such as MF59 and AS03, which are currently used for human influenza vaccines . Despite this widespread use of squalene, the mechanisms via which it favors Toll‐like receptor (TLR) agonists and enhances adaptive immune responses are not fully understood.…”
Section: Squalene and The Immune Systemmentioning
confidence: 99%
“…MF59 and Alum facilitate APCs to engulf antigens and transport them to draining lymph nodes (dLNs), and also induce the differentiation of monocytes to dendritic cells (Mo-DCs) 36, 37 . So, we next evaluated antigen uptake by APCs and Mo-DC differentiation in dLNs after MnJ administration.…”
Section: Resultsmentioning
confidence: 99%
“…The adjuvant activity of Aluminum was found by Alexander Glenny and his colleagues in 1926 41 , now almost one century later, we reported the adjuvant activity of another metal-Manganese. Adjuvant effect is essentially attributed by type I-IFN-promoted dendritic cell maturation and migration to prime adaptive immune responses along with 1) local up-regulation of chemokines, including CCL2 (MCP-1) and CCL3 (MIP-1α) to recruit immune cells to the injection site; 2) increase of antigen uptake by immune cells; 3) induction of monocyte differentiation into dendritic cells 8, 36, 37 . We found that Mn 2+ induced APCs to produce both IFNβ and various IFNαs, which were surprisingly not induced by LPS, together with many co-stimulatory and MHC molecules crucial for antigen presentation and chemokines for immune cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Recently, MF59 was shown to promote differentiation of monocytederived DCs (Mo-DCs) within draining lymph nodes and these Mo-DCs were the major APCs to enhance antigen-specific CD4 T cell responses. 11 In addition, MF59 enhanced CD4 T follicular helper cell activation and following germinal center reaction to increase B cell responses in mice. 12 CD4 T cells are required for inducing B cell responses to generate isotype-switched IgG antibodies to subunit split virus or protein antigen vaccination.…”
Section: Cd4-dependent and Cd4-independent Adjuvant Effects Of Mf59mentioning
confidence: 99%